The impact of time-integrated active or passive sampling methods on bioanalytical water quality risk assessment - Ron van der Oost; Jaap Postma; Willie van den Berg; Mai Thao Nguyen; Insam al Saify; Corine J. Houtman; Harrie Besselink; Evert-Jan van den Brandhof; Abraham Brouwer (Journal of Water Process Engineering, 2026)

Factors influencing submerged macrophyte presence in fresh and brackish eutrophic waters and their impact on carbon emissions - Thomas Gremmen; Gijs van Dijk; Jaap Postma; Maite Colina; Lisette N. de Senerpont Domis; Mandy Velthuis; Rob van de Haterd; Fred Kuipers; Huibert van Rossum; Alfons J.P. Smolders; Sarian Kosten (Aquatic Botany, 2023)

Reduced tillage increases soil biological properties but not suppressiveness against Rhizoctonia solani and Streptomyces scabies - Viola Kurm; Mirjam T. Schilder; Wiepie K. Haagsma; Jaap Bloem; Olga E. Scholten; Joeke Postma (Applied Soil Ecology, 2023)

EPMA-World Congress 2015 - Jella-Andrea Abraham; Olga Golubnitschaja; Ildar Akhmetov; Russell J. Andrews; Leonidas Quintana; Russell J. Andrews; Babak Baban; Jun Yao Liu; Xu Qin; Tailing Wang; Mahmood S. Mozaffari; Viktoriia V. Bati; et al. (EPMA Journal, 2016)

Shared and distinct anatomical correlates of semantic and phonemic fluency revealed by lesion-symptom mapping in patients with ischemic stroke - J. Matthijs Biesbroek; Martine J. E. van Zandvoort; L. Jaap Kappelle; Birgitta K. Velthuis; Geert Jan Biessels; Albert Postma (Brain Structure and Function, 2016)

Effects of Seven Fungicides on Non-Target Aquatic Fungi - Jan Dijksterhuis; Tineke van Doorn; Rob Samson; Jaap Postma (Water, Air, & Soil Pollution, 2011)

Soil biota community structure and abundance under agricultural intensification and extensification - Maria B. Postma-Blaauw; Ron G. M de Goede; Jaap Bloem; Jack H. Faber; Lijbert Brussaard (Ecology, 2010)
Understanding the impacts of agricultural intensification and extensification on soil biota communities is useful in order to preserve and restore biological diversity in agricultural soils and enhance the role of soil biota in agroecosystem functioning. Over four consecutive years, we investigated the effects of agricultural intensification and extensification (including conversion of grassland to arable land and vice versa, increased and decreased levels of mineral fertilization, and monoculture compared to crop rotation) on major soil biota group abundances and functional diversity. We integrated and compared effects across taxonomic levels to identify sensitive species groups. Conversion of grassland to arable land negatively affected both abundances and functional diversity of soil biota. Further intensification of the cropping system by increased fertilization and reduced crop diversity exerted smaller and differential effects on different soil biota groups. Agricultural intensification affected abundances of taxonomic groups with larger body size (earthworms, enchytraeids, microarthropods, and nematodes) more negatively than smaller‐sized taxonomic groups (protozoans, bacteria, and fungi). Also functional group diversity and composition were more negatively affected in larger‐sized soil biota (earthworms, predatory mites) than in smaller‐sized soil biota (nematodes). Furthermore, larger soil biota appeared to be primarily affected by short‐term consequences of conversion (disturbance, loss of habitat), whereas smaller soil biota were predominantly affected by long‐term consequences (probably loss of organic matter). Reestablishment of grassland resulted in increased abundances of soil biota groups, but since not all groups increased in the same measure, the community structure was not completely restored. We concluded that larger‐sized soil biota are more sensitive to agricultural intensification than smaller‐sized soil biota. Furthermore, since larger‐sized soil biota groups had lower taxonomic richness, we suggest that agricultural intensification exerts strongest effects on species‐poor soil biota groups, thus supporting the hypothesis that biodiversity has an “insurance” function. As soil biota play an important role in agroecosystem functioning, altered soil biota abundances and functional group composition under agricultural intensification are likely to affect the functioning of the agroecosystem.

NETMORPH: A Framework for the Stochastic Generation of Large Scale Neuronal Networks With Realistic Neuron Morphologies - Randal A. Koene; Betty Tijms; Peter van Hees; Frank Postma; Alexander de Ridder; Ger J. A. Ramakers; Jaap van Pelt; Arjen van Ooyen (Neuroinformatics, 2009)

Ammonium Toxicity at High pH in a Marine Bioassay Using Corophium volutator - Belinda J. Kater; Marco Dubbeldam; Jaap F. Postma (Archives of Environmental Contamination and Toxicology, 2006)

Seasonal dynamics and larval drift of Chironomus riparius (Diptera) in a metal contaminated lowland river - Dick Groenendijk; Jaap F. Postma; Michiel H.S. Kraak; Wim Admiraal (Aquatic Ecology, 1998)